Blamada rubripronota, a new genus and species of the tribe Saperdini (Coleoptera: Cerambycidae: Lamiinae) from Southeast Asia - Lin, Mei-Ying; Holzschuh, Carolus (Zootaxa, 2013)
A new saperdine species belonging to a new genus, Blamada rubripronota gen. et sp. nov., is described from Laos, Viet-nam and China. The genus differs from other genera of the tribe Saperdini in having the antennal scape bearing an expand-ed and ridged ring at apex, and second antennomere relatively longer (more than 1/4 of scape in length) than that of other saperdine taxa.